Effects of aquaculture on the maintenance of waterbird populations. Issue 5 (20th May 2022) - Cheng, Chuyu; Liu, Jiajia; Ma, Zhijun
Abstract: The global aquaculture industry has expanded rapidly and is increasingly important for maintaining food security and providing habitat for many waterbirds. Clarifying how waterbirds use aquafarms and how aquafarm use affects waterbird population maintenance can help improve management of the aquafarm landscape such that it can provide habitat for waterbirds. We investigated aquafarm use by waterbirds in China, the world's largest producer of aquaculture products. We used data from the literature on and expert knowledge (questionnaire survey) of waterbird use of aquafarms in China and Bayesian phylogenetic generalized linear mixed models to analyze the relationship between the degree of aquafarm use and population trends of waterbirds. Sixty‐nine percent of waterbird species in China have been recorded at aquafarms. Approximately one quarter of all waterbird species and about the same proportion of threatened species were found to forage at aquafarms, consuming either cultured aquatic products or other food stuffs. In general, species with a high degree of aquafarm use were unlikely to exhibit a population decline over the past 2 decades, when rapid loss of natural habitat occurred in China. This relationship was not detected in threatened species, despite there being no significant difference in the degree of aquafarm use between threatened and nonthreatened species. Our results suggest that the large and expanding aquaculture industry is important for maintaining waterbird populations in China. However, aquafarms are not a replacement for natural habitats because threatened species benefited less from aquafarm use. Given that aquafarms often negatively affect natural wetlands, the degree to which aquafarms compensate for natural habitat loss probably depends on the quality of aquafarm habitat and the habitat requirements of waterbirds. We recommend an integrated ecological and economic analysis to formulate management policies that help conserve wildlife within the constraints and opportunities associated with maintaining human livelihoods. Abstract : Article Impact Statement : Aquafarms help maintain many but not all waterbird populations, and improving their habitat quality may modulate the impacts of habitat loss. Abstract : Efectos de la Acuacultura sobre la Conservación de las Poblaciones de Aves Acuáticas Resumen: La industria mundial de la acuacultura se ha expandido rápidamente y cada vez es más importante para conservar la seguridad alimenticia y proporcionar hábitats para muchas aves acuáticas. Si se aclara cómo usan las aves acuáticas las granjas de acuacultura y cómo el éstas afectan a la conservación de las poblaciones de estas aves, se puede mejorar la gestión de los terrenos de acuacultura de tal manera que proporcionen un hábitat para las aves acuáticas. Investigamos el uso que las aves acuáticas le dan a las granjas de acuacultura en China, el mayor productor a nivel mundial de productos de acuicultivo. Usamos datos tomados de la literatura sobre el uso que le dan las aves acuáticas a los cultivos acuáticos en China y el conocimiento de expertos (cuestionario) y modelos bayesianos mixtos de la filogenia generalizada para analizar las relaciones entre el nivel de uso de la granja acuícola y las tendencias poblacionales de las aves acuáticas. El 69% de las especies de aves acuáticas en China se ha registrado en estas granjas. Descubrimos que aproximadamente un cuarto de todas las especies de aves acuáticas y casi la misma proporción de especies amenazadas se alimentan en las granjas acuícolas, en donde consumen los productos del cultivo o u otros alimentos. En general, las especies con un nivel elevado de uso de las granjas acuícolas no tuvieron probabilidad de declinar a nivel poblacional durante las dos últimas décadas, un momento en el que ocurrió una pérdida rápida de hábitats en China. No se detectó esta relación en las especies amenazadas, a pesar de que no hubo una diferencia importante entre las especies amenazadas y las no amenazadas. Nuestros resultados sugieren que la enorme y creciente industria de la acuacultura es importante para la conservación de las poblaciones de aves acuáticas en China. Sin embargo, las granjas acuícolas no sustituyen a los hábitats naturales ya que las especies amenazadas tuvieron menos beneficios al usarlas. Ya que las granjas acuícolas con frecuencia afectan negativamente a los humedales, el grado al que estas granjas compensan la pérdida del hábitat natural probablemente depende de la calidad del hábitat artificial. Recomendamos un análisis económico y ecológico integrado para formular políticas de manejo que ayuden a conservar la fauna dentro de las restricciones y oportunidades asociadas con la preservación de los medios de subsistencia humanos. 摘要: 在过去几十年里, 全球水产养殖业发展迅速, 除了在保障食品供给和促进经济发展方面发挥着关键作用外, 水产养殖场所还为许多水鸟提供了人工栖息地。了解水鸟如何利用水产养殖场所, 以及利用水产养殖场所如何影响水鸟的种群趋势, 有助于人工栖息地的管理。本文以全球最大的水产养殖国——中国为例, 通过文献收集和问卷调查, 发现有 69% 的水鸟种类在水产养殖场所被记录到。其中, 分别有四分之一的水鸟和受胁水鸟在水产养殖场所觅食, 取食水产品或其它食物。总体而言, 在自然栖息地迅速减少的过去 20 年间, 对水产养殖场所利用程度越高的水鸟, 种群数量下降的可能性越低。尽管受胁和非受胁物种对水产养殖场所的利用程度没有显著差异, 但是受胁物种对水产养殖场所的利用程度与种群趋势并无显著的相关性。本研究表明, 水产养殖对许多水鸟, 但不是所有水鸟, 的种群维持有重要作用。然而, 水产养殖场所不能替代自然湿地的栖息地功能, 因为受胁物种从利用水产养殖场所中受益较少。特别是鉴于水产养殖场所的建立通常是以自然湿地的丧失为代价, 其对水鸟种群维持的补偿作用取决于水产养殖场所的栖息地质量和水鸟的栖息地需求。我们强调未来基于综合的生态和经济分析来制定水产养殖业发展和水产养殖场所管理的政策, 在服务于经济和社会发展的同时提升生物多样性保护的功能。 题目 :水鸟对水产养殖场所的利用及其对种群维持的作用